2021
DOI: 10.1002/hep4.1647
|View full text |Cite
|
Sign up to set email alerts
|

Human Nonalcoholic Steatohepatitis on a Chip

Abstract: Nonalcoholic steatohepatitis (NASH), an advanced stage of nonalcoholic fatty liver disease (NAFLD), is a rapidly growing and global health problem compounded by the current absence of specific treatments. A major limiting factor in the development of new NASH therapies is the absence of models that capture the unique cellular structure of the liver microenvironment and recapitulate the complexities of NAFLD progression to NASH. Organ-on-a-chip platforms have emerged as a powerful approach to dynamically model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…5(e) ]. 113 Four types of primary cells were co-cultured with stable viability, and it was confirmed that liver-specific albumin and urea secretion function was improved. NASH was induced by exposure to FFA and LPS, and expression levels were observed by analyzing inflammatory markers MCP1, TNF-alpha, TGF-beta, and OPN.…”
Section: Liver Disease Modelsmentioning
confidence: 84%
See 1 more Smart Citation
“…5(e) ]. 113 Four types of primary cells were co-cultured with stable viability, and it was confirmed that liver-specific albumin and urea secretion function was improved. NASH was induced by exposure to FFA and LPS, and expression levels were observed by analyzing inflammatory markers MCP1, TNF-alpha, TGF-beta, and OPN.…”
Section: Liver Disease Modelsmentioning
confidence: 84%
“…Copyright 2021 John Wiley and Sons. 113 (f) HBV was induced in liver-on-a-chip by transfection with HBV-genome cDNA and virus genome expressed from recombinant adenovirus. Reproduced with permission from Kang et al , Biotechnol.…”
Section: Liver Disease Modelsmentioning
confidence: 99%
“…Through a 21-day life-span, the system recapitulated NASH features and showed neovascularization. Freag et al. (2021) also developed an on-chip model by co-culturing primary human hepatic cell lines (hepatocytes, KC, HSC and LSEC).…”
Section: D Tissue Culture Models In Nafldmentioning
confidence: 99%
“…More recently, a model was created to use alcohol as an inductor to study biomarkers such as oxidative stress and lipid accumulation and to generate a novel in vitro quantitative readout of alcoholic liver toxicity by measuring structural changes of the bile canaliculi network (Nawroth et al 2020). There are also models for the study of NAFLD, which comprises different stages, from steatosis to steatohepatitis, cirrhosis and hepatocellular carcinoma (Gori et al 2016;Bulutoglu et al 2019;Cho et al 2021;Freag et al 2021).…”
Section: Gut-associated Disease Models Based On the Organ-on-a-chip Technology And Their Clinical Significancementioning
confidence: 99%